Facets of personality linked to underweight and overweight - Terracciano, Antonio; Sutin, Angelina R; McCrae, Robert R; Deiana, Barbara; Ferrucci, Luigi; Schlessinger, David; Uda, Manuela; Costa, Jr, Paul T (Psychosomatic medicine, 2009)
Personality traits underlie maladaptive behaviors, and cognitive and emotional disturbances that contribute to major preventable causes of global disease burden. This study examines detailed personality profiles of underweight, normal, and overweight individuals to provide insights into the causes and treatments of abnormal weight. More than half of the population from four towns in Sardinia, Italy (n = 5693; age = 14-94 years; mean +/- standard deviation = 43 +/- 17 years) were assessed on multiple anthropometric measures and 30 facets that comprehensively cover the five major dimensions of personality, using the Revised NEO Personality Inventory. High Neuroticism and low Conscientiousness were associated with being underweight and obese, respectively. High Impulsiveness (specifically eating-behavior items) and low Order were associated with body mass index categories of overweight and obese, and with measures of abdominal adiposity (waist and hip circumference). Those scoring in the top 10% of Impulsiveness were about 4 kg heavier than those in the bottom 10%, an effect independent and larger than the FTO genetic variant. Prospective analyses confirmed that Impulsiveness and Order were significant predictors of general and central measures of adiposity assessed 3 years later. Overweight and obese individuals have difficulty resisting cravings and lack methodical and organized behaviors that might influence diet and weight control. Although individuals' traits have limited impact on the current obesogenic epidemic, personality traits can improve clinical assessment, suggest points of intervention, and help tailor prevention and treatment approaches.